Osmotic controlled drug delivery system (OSMO technology) and its impact on diabetes care - Rajput, Rajesh; Kumar, K. M. K. Prasanna; Arya, D. S.; Das, A. K.; Zargar, A. H.; Tiwaskar, Mangesh; Motghare, Vijay; Shah, Ruchi; Ingole, Shahu; Jain, Rishi (International Journal of Research in Medical Sciences, 2020)
Recently, focus on the development of controlled release drug delivery system has increased, as existing drugs exhibit certain pharmacokinetic limitations. The major goal of designing sustained release formulations is to improve the drug performance by prolonged duration of drug action, decreased frequency of dosing and reduced side effects by using smallest quantity of drug administered by the most suitable route. Osmotic-controlled release oral delivery system (OSMO technology) is the most promising strategy based system for sustained delivery of drug. Drug can be delivered in a controlled manner over a long period of time by the process of osmosis. Osmotic drug delivery system appears to be a promising solution for the limitations of conventional extended release formulations by virtue of their distinguished technological features. The present review describes briefly about various controlled drug delivery systems with special focus on advantages of osmotic-controlled release oral delivery system related to diabetes therapy and improved compliance.